'Come out, come out, whoever you are!' Client perceptions of working alliance following imagined sexual identity disclosure in coaching. Issue 2 (2nd July 2020) - Ghama, Issome; Spence, Gordon B.
ABSTRACT: Whilst the relationship between working alliance and sexual identity disclosure has received some empirical attention in the psychotherapeutic literature, it has yet to be examined in coaching contexts. To commence the exploration of sexual identity issues in coaching, a pilot study ( n  = 40) was designed to investigate the extent to which an imagined disclosure experience would impact upon participants' perceptions of working alliance. Two hypothesises were tested using a vignette-based survey. The first predicted that both working alliance and disclosure intentions would be related to the anticipated support of a coach. The second hypothesis predicted that imagined sexual identity disclosure to a coach would have a positive impact on perceived working alliance. Whilst a correlational analysis found support for the first hypothesis, the pattern of relationships differed for the two anticipated support variables: coach comfort and coach support . The second hypothesis was tested using a simple vignette manipulation and pre-post disclosure measures. Participants reported a strengthening of perceived working alliance after considering the disclosure scenario ( t  = −2.30, p  < .05). A discussion of the results is then presented and related to recent evidence confirming the importance of autonomy support to disclosure decisions and their long-term impact. Implications for coaching research and practice are provided.